Coastal evidence for Holocene subduction-zone earthquakes and tsunamis in central Chile - Dura, Tina; Cisternas, Marco; Horton, Benjamin P.; Ely, Lisa L.; Nelson, Alan R.; Wesson, Robert L.; Pilarczyk, Jessica E. (Quaternary Science Reviews, 2015)
The ∼500-year historical record of seismicity along the central Chile coast (30–34°S) is characterized by a series of ∼M 8.0–8.5 earthquakes followed by low tsunamis (<4 m) occurring on the megathrust about every 80 years. One exception is the AD 1730 great earthquake (M 9.0–9.5) and high tsunami (>10 m), but the frequency of such large events is unknown. We extend the seismic history of central Chile through a study of a lowland stratigraphic sequence along the metropolitan coast north of Valparaíso (33°S). At this site, higher relative sea level during the mid Holocene created a tidal marsh and the accommodation space necessary for sediment that preserves earthquake and tsunami evidence. Within this 2600-yr-long sequence, we traced six laterally continuous sand beds probably deposited by high tsunamis. Plant remains that underlie the sand beds were radiocarbon dated to 6200, 5600, 5000, 4400, 3800, and 3700 cal yr BP. Sediment properties and diatom assemblages of the sand beds—for example, anomalous marine planktonic diatoms and upward fining of silt-sized diatom valves—point to a marine sediment source and high-energy deposition. Grain-size analysis shows a strong similarity between inferred tsunami deposits and modern coastal sediment. Upward fining sequences characteristic of suspension deposition are present in five of the six sand beds. Despite the lack of significant lithologic changes between the sedimentary units under- and overlying tsunami deposits, we infer that the increase in freshwater siliceous microfossils in overlying units records coseismic uplift concurrent with the deposition of five of the sand beds. During our mid-Holocene window of evidence preservation, the mean recurrence interval of earthquakes and tsunamis is ∼500 years. Our findings imply that the frequency of historical earthquakes in central Chile is not representative of the greatest earthquakes and tsunamis that the central Chilean subduction zone has produced.
Keywords: Coastal hazards; Coastal paleoseismology; Diatom paleoecology; Prehistoric earthquakes; Tsunami Deposits